2021
DOI: 10.1097/brs.0000000000004203
|View full text |Cite
|
Sign up to set email alerts
|

Single Impact Injury of Vertebral Endplates Without Structural Disruption, Initiates Disc Degeneration Through Piezo1 Mediated Inflammation and Metabolism Dysfunction

Abstract: This in vitro experimental study demonstrated that not only structural disruption, but also a single impact injury of the endplate without structural impairment could also initiate intervertebral disc degeneration (IDD), which might be mediated by activation of Piezo1 induced inflammation and abnormal energy metabolism of intervertebral disc cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
(78 reference statements)
2
15
0
Order By: Relevance
“…Consistent with previous studies, matrix metalloproteinase-3 (MMP3) was also found to be highly expressed in the inflammatory response NPC cluster (IR NPC), which accounted for a highly proportion of NP cells in the late stage of IDD. This is also consistent with our previous study that has demonstrated that inflammation was one of the main contributors to IDD ( Molinos et al, 2015 ; Wei et al, 2015 ; Wei et al, 2019 ; Sun et al, 2021 ). Further analysis showed that the gene thioredoxin-interacting protein (TXNIP), early growth response 1 (ERG1), and fibroblast growth factor 1 (FGF1) were also highly expressed in this cluster.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with previous studies, matrix metalloproteinase-3 (MMP3) was also found to be highly expressed in the inflammatory response NPC cluster (IR NPC), which accounted for a highly proportion of NP cells in the late stage of IDD. This is also consistent with our previous study that has demonstrated that inflammation was one of the main contributors to IDD ( Molinos et al, 2015 ; Wei et al, 2015 ; Wei et al, 2019 ; Sun et al, 2021 ). Further analysis showed that the gene thioredoxin-interacting protein (TXNIP), early growth response 1 (ERG1), and fibroblast growth factor 1 (FGF1) were also highly expressed in this cluster.…”
Section: Discussionsupporting
confidence: 94%
“…A single impact applied to the lumbar disc without causing structural damage to the lumbar spine also triggered significant upregulation of Piezo1, NLRP3 inflammatory vesicles, catabolic (MMP-9, MMP-13) and pro-inflammatory gene (IL-1β) expression and induced disc degeneration (IDD). Piezo1 inhibition reduces mechanical shock-induced activation of NLRP3 inflammasome and IL-1β expression in nucleus pulposus cells ( 95 ). In addition, G protein-coupled estrogen receptor attenuates mechanical stress-mediated apoptosis of chondrocytes in osteoarthritis via suppression of Piezo1 ( 96 ).…”
Section: Piezo1 Channel-mediated Chronic Inflammationmentioning
confidence: 99%
“…The function of Piezo1 and its downstream mechanism have obvious differences in various tissue inflammations. Piezo1-mediated Ca 2+ signaling participates in the occurrence and development of inflammation through a variety of signaling pathways ( Table 1 ), including the classic inflammation pathway Jak/Stat: IL-6 receptor family ( 56 , 120 ), TLR ( 9 , 42 ) and NF-κB ( 66 , 117 , 121 ); Inflammasome NLRP3 ( 66 , 95 ); Ca 2+ -sensitive MAPK family (ERK, JNK, P38) ( 116 , 120 , 122 , 123 ), AKT/mTOR ( 60 , 69 )、β1 integrin ( 18 ); As well as focal adhesion kinase (FAK) related to inflammation-related mechanical transformation ( 60 , 124 ), proline-rich tyrosine kinase2 (Pyk2) ( 125 ); Calcineurin (RACK1), calcium/calmodulin-dependent protein kinase II (CaMKII-Mst1/2-Rac) and calpain1 ( 18 ). Although the downstream mechanisms involved in Piezo1 are different in different organizations and occasions, they all eventually lead to inflammatory events.…”
Section: Mechanism Of Piezo1 Transducing Inflammatory Signalsmentioning
confidence: 99%
“…Despite its regular occurrence over a lifetime, it is currently uncertain if IVDD can be initiated by Piezo1 under excessive stress. As for the role of Piezo1 in the IVDD process, Sun et al [ 30 ] reported that a single impact injury without structural impairment, similar to axial stress, can promote inflammatory response during IVDD process via Piezo1 activation. Moreover, Sun et al [ 31 ] demonstrated Piezo1 sensitization induced by mechanical stretch also increased the NLPR3 inflammasome in NP cells.…”
Section: Discussionmentioning
confidence: 99%